Genome Sequence Variations of Infectious Bronchitis Virus Serotypes From Commercial Chickens in Mexico - Kariithi, Henry M.; Volkening, Jeremy D.; Leyson, Christina M.; Afonso, Claudio L.; Christy, Nancy; Decanini, Eduardo Lucio; Lemiere, Stéphane; Suarez, David L. (Frontiers in Veterinary Science, 2022)
New variants of infectious bronchitis viruses (IBVs; Coronaviridae) continuously emerge de-spite routine vaccinations. Here, we report genome sequence variations of IBVs identified by random nontargeted next generation sequencing (NGS) of vaccine and field samples collected on FTA cards from commercial flocks in Mexico in 2019-2021. Paired-ended sequencing libraries prepared from rRNA-depleted RNAs were sequenced using Illumina MiSeq. IBV RNA was detected in 60.07% (n=167) of the analyzed samples, from which 33 complete genome sequences were de novo assembled. The genomes are organized as 5’UTR-[Rep1a-Rep1b-S-3a-3b-E-M-4b-4c-5a-5b-N-6b]-3’UTR, except in eight sequences lacking non-structural protein genes (accessory genes) 4b, 4c and 6b. Seventeen sequences have auxiliary S2’ cleavage site located 153 residues downstream the canonically conserved primary furin-specific S1/S2 cleavage site. The sequences distinctly cluster into lineages GI-1 (Mass-type; n=8), GI-3 (Holte/Iowa-97; n=2), GI-9 (Arkansas-like; n=8), GI-13 (793B; n=14), and GI-17 (California variant; CAV; n=1), with regional distribution in Mexico; this is the first report of the presence of 793B- and CAV-like strains in the country. Various point mutations, substitutions, insertions and deletions are pre-sent in the S1 hypervariable regions (HVRs I-III) across all 5 lineages, including in residues 38, 43, 56, 63, 66 and 69 that are critical in viral attachment to respiratory tract tissues. Nine intra-/inter-lineage recombination events are present in the S proteins of three Mass-type sequences, two each of Holte/Iowa-97 and Ark-like sequence, and one each of 793B-like and CAV-like sequences. This study demonstrates the feasibility of FTA cards as an attractive, adoptable low-cost sampling option for untargeted discovery of avian viral agents in field-collected clinical samples. Collectively, our data points to co-circulation of multiple distinct IBVs in Mexican commercial flocks, underscoring the need for active surveillance and a review of IBV vaccines currently used in Mexico and the larger Latin America region.